1995
DOI: 10.1177/0743554895102005
|View full text |Cite
|
Sign up to set email alerts
|

Peer Relationships as a Source of Support for Adolescent Mothers

Abstract: Little has been written about the role of the peer group in the lives of adolescent mothers. There has been speculation that an adolescent mother's peer relationships change as a result of pregnancy andparenthood. The literature indicates that peers become less able to provide a support system. Little empirical evidence has been provided to support this speculation. This study assessed a sample of 46 adolescent mothers on the amounts and types of supportprovided byfriends as compared to relatives and examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 18 publications
3
17
0
2
Order By: Relevance
“…The role of peer support and well-being among pregnant/parenting teens is an area of research that has received less attention than that of family or partner support. Several studies found peer support to be significantly associated with reduced depression and social isolation and increased life satisfaction among teen mothers (Richardson, Barbour, & Bubenzer, 1995;Voight, Hans, & Bernstein, 1996). However, Gee and Rhodes (2007) found that peer support was not associated with teen mothers' well-being.…”
Section: Discussionmentioning
confidence: 94%
“…The role of peer support and well-being among pregnant/parenting teens is an area of research that has received less attention than that of family or partner support. Several studies found peer support to be significantly associated with reduced depression and social isolation and increased life satisfaction among teen mothers (Richardson, Barbour, & Bubenzer, 1995;Voight, Hans, & Bernstein, 1996). However, Gee and Rhodes (2007) found that peer support was not associated with teen mothers' well-being.…”
Section: Discussionmentioning
confidence: 94%
“…The social support‐parenting stress link is particularly important for identifiable high‐risk groups of parents. Adolescent mothers are at risk for high levels of parenting stress (Passino et al, 1993), but emotional support, and in particular support from friends, is related to lower parenting stress for these young mothers (Richardson, Bar‐bour, & Bubenzer, 1995). Social support may also be associated with lower parenting stress among other risk groups, such as economically disadvantaged parents (Ada‐makos et al, 1986) and parents of chronically ill or handicapped children (Frey et al, 1989; Hauenstein, 1990).…”
Section: A General Theory Of Parenting Stressmentioning
confidence: 99%
“…However, while these studies provide a positive perspective on peer support the issue is explored only as a minor aspect of wider support networks. Richardson et al . 's (1995) research differs in that it focuses specifically on peer support and provides a comparative analysis with family support.…”
Section: Peer Supportmentioning
confidence: 99%